2015
DOI: 10.4236/ojs.2015.52016
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference of Spatially Correlated Binary Data Using Skew-Normal Latent Variables with Application in Tooth Caries Analysis

Abstract: The analysis of spatially correlated binary data observed on lattices is an interesting topic that catches the attention of many scholars of different scientific fields like epidemiology, medicine, agriculture, biology, geology and geography. To overcome the encountered difficulties upon fitting the autologistic regression model to analyze such data via Bayesian and/or Markov chain Monte Carlo (MCMC) techniques, the Gaussian latent variable model has been enrolled in the methodology. Assuming a normal distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…According to the values of these indicators the spatial model (MICAR-skew-normal) that assumes the structured spatial components are drawn from multivariate skew-normal distribution appears to perform better than the MICAR-normal model; suggesting that the MICAR-skew-normal model has a better predictive capacity and fits the skew-normal multivariate intrinsic conditional autoregressive spatial model and its application for disease mapping district ART coverage and knowledge of HIV status data better as compared to the MICAR-normal model. A similar study conducted by Afroughi et al (2015) indicated that a skew-normal distribution assumption to the spatially structured components fits the data well as compared to its normal counterpart. The skewness parameters are not significantly different from zero for both outcome variables suggesting little evidence of heavy tails; however as indicated above the MICAR-skew-normal model performs better than the MICAR-normal which supports our argument that our proposed approach should also be considered as alternative method in spatial modelling.…”
Section: Discussionmentioning
confidence: 76%
“…According to the values of these indicators the spatial model (MICAR-skew-normal) that assumes the structured spatial components are drawn from multivariate skew-normal distribution appears to perform better than the MICAR-normal model; suggesting that the MICAR-skew-normal model has a better predictive capacity and fits the skew-normal multivariate intrinsic conditional autoregressive spatial model and its application for disease mapping district ART coverage and knowledge of HIV status data better as compared to the MICAR-normal model. A similar study conducted by Afroughi et al (2015) indicated that a skew-normal distribution assumption to the spatially structured components fits the data well as compared to its normal counterpart. The skewness parameters are not significantly different from zero for both outcome variables suggesting little evidence of heavy tails; however as indicated above the MICAR-skew-normal model performs better than the MICAR-normal which supports our argument that our proposed approach should also be considered as alternative method in spatial modelling.…”
Section: Discussionmentioning
confidence: 76%